Peran Perempuan dalam Meriwayatkan Hadits: Studi Pustaka atas Aisyah r.a Binti Abu Bakar - Annisaa Siti Zuadah (Gunung Djati Conference Series, 2023)
The purpose of this study is to discuss the role of women in transmitting hadith. By using a descriptive-analytical method, this research also uses a qualitative methodology. The formal object of this research is the science of hadith and the material object is the role of women in transmitting hadith. The results and discussion of this study indicate that women have played a role since the time of the Prophet Muhammad, in spreading Islamic knowledge, this shows the importance of women's position. This study came to the conclusion that one way for women to pass down hadith is in a way that reflects the principles of Islamic education. Aisyah r.a., one of the figures, who contributed to the hadith narration process which is very useful for understanding Islamic sciences.